(untitled) (Journal of Enam Medical College, 2019)
Background: During last 2−3 decades image-guided drainage procedures have been developed complementing modern surgical drainage techniques. The development of interventional radiological procedure has made percutaneous puncture and drainage of abdominal fluid collection possible. Image-guided percutaneous drainage of appendicular abscess has become well-established because of its proven safety and efficacy. Objectives: To evaluate the safety and feasibility of USG-guided percutaneous aspiration for draining appendicular abscess with special attention to the need for conversion and to see the nature of complications after draining of abscess. Materials and Methods: Between May 2013 to May 2014, 25 cases of appendicular abscess were selected from the admitted patients (surgery department) in Enam Medical College & Hospital who underwent USG-guided percutaneous aspiration. Procedure was performed mostly under local anaesthesia. Patients were followed up for 6 months. Interval appendicectomy was not performed routinely. Results: USG-guided aspiration was successful in 23 (92%) patients and in 2 (8%) patients procedure failed. Single attempt was successful in 21 (84%) cases and 4 (16%) patients needed double attempt for draining appendicular abscess. In 23 (92%) patients, PCA was done under local anaesthesia and two (8%) patients needed general anaesthesia. Complications developed in 4 (16%) patients. Four (16%) patients needed follow-up USG. Average hospital stay was 5 days (2−8 days) and average duration of using I/V antibiotic was 3.5 days (2−5 days). Conclusion: USG-guided percutaneous aspiration is an easy and safe method for draining appendicular abscess with minimum procedural complications. J Enam Med Col 2019; 9(1): 41-45